2011
DOI: 10.1021/om2000458
|View full text |Cite
|
Sign up to set email alerts
|

Disambiguation of Metal and Brønsted Acid Catalyzed Pathways for Hydroarylation with Platinum(II) Catalysts

Abstract: The hydroarylation of unactivated olefins effected by Pt(II) precatalysts was found to proceed through the in situ production of protic acid followed by a Friedel−Crafts mechanism. The reaction was investigated using the hindered base 2,6-di-tert-butyl-4-methylpyridine and a variety of substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 18 publications
(51 reference statements)
1
33
0
Order By: Relevance
“…22,29 Particularly germane is a recent study that reveals catalytic olefin hydroarylation using Pt(II) triflate salts likely proceeds by formation of triflic acid, which serves as the active catalyst. 30 Our groups reported a series of studies on TpRu(L)(NCMe)-(Ph) [Tp = hydridotris(pyrazolyl)borate, L = CO, PMe 3 , P(Npyrrolyl) 3 , or P(OCH 2 ) 3 CEt] catalysts for olefin hydroarylation. 18,19,23À26,31 The primary focus has been to elucidate the effect of the donor and steric properties of the ligand L on the key steps of the catalytic cycle (i.e., olefin insertion and aromatic/ olefin CÀH activation).…”
Section: à26mentioning
confidence: 99%
See 1 more Smart Citation
“…22,29 Particularly germane is a recent study that reveals catalytic olefin hydroarylation using Pt(II) triflate salts likely proceeds by formation of triflic acid, which serves as the active catalyst. 30 Our groups reported a series of studies on TpRu(L)(NCMe)-(Ph) [Tp = hydridotris(pyrazolyl)borate, L = CO, PMe 3 , P(Npyrrolyl) 3 , or P(OCH 2 ) 3 CEt] catalysts for olefin hydroarylation. 18,19,23À26,31 The primary focus has been to elucidate the effect of the donor and steric properties of the ligand L on the key steps of the catalytic cycle (i.e., olefin insertion and aromatic/ olefin CÀH activation).…”
Section: à26mentioning
confidence: 99%
“…82 Evidence that the hydroarylation of cyclohexene using L 2 Pt(OTf) 2 (L 2 = 1,5-cyclooctadiene or t bpy, OTf = trifluoromethanesulfonate) likely proceeds via the generation of HOTf, which is the active catalyst, has been disclosed. 30 The hydrophenylation of ethylene (0.1 MPa) using 0.025 mol % HBAr 0 4 results in ∼1 TO of ethylbenzene after 16 h at 120°C. In addition, catalysis with 1 in the presence of 2,6-di-tert-butyl-4-methylpyridine (1.5 equiv relative to 1), which gave 16.8 TO of ethylbenzenes after 4 h, was not suppressed.…”
Section: 61à67mentioning
confidence: 99%
“…[11][12][13][14][15] As part of our ongoing interest in the noble metalcatalyzed hydrofunctionalization of C-C multiple bonds, [16] we have shown that PtCl 2 catalyzes the intermolecular hydroarylation of vinyl arenes, as well as ethylene and propene, with indoles. [14,[17][18][19][20][21][22][23] For example, treatment of a 3 : 1 mixture of p-chlorostyrene (1 a) with 1,2-dimethylindole (2) and a catalytic amount of PtCl 2 (5 mol %) in dioxane at 120°C led to isolation of a 1.6 : 1 mixture of the anti-Markovnikov hydroarylation product 3 a and the Markovnikov hydroarylation product 4 a along with traces (~5 %) of the Markovnikov alkenylation product 5 a in 89 % combined yield (Scheme 1). [14,24,25] The anti-Markovnikov/Markovnikov selectivity of the Pt-catalyzed hydroarylation of p-substituted vinyl arenes 1 with 2 increased from 0.5 : 1 for p-methylstyrene to 5.8 : 1 for p-nitrostyrene and the log of the Markovnikov/anti-Markovnikov ratio tracked linearly with the Hammett σparameter (ρ = À 0.98).…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing interest in the noble metal‐catalyzed hydrofunctionalization of C–C multiple bonds, we have shown that PtCl 2 catalyzes the intermolecular hydroarylation of vinyl arenes, as well as ethylene and propene, with indoles . For example, treatment of a 3 : 1 mixture of p ‐chlorostyrene ( 1 a ) with 1,2‐dimethylindole ( 2 ) and a catalytic amount of PtCl 2 (5 mol %) in dioxane at 120 °C led to isolation of a 1.6 : 1 mixture of the anti ‐Markovnikov hydroarylation product 3 a and the Markovnikov hydroarylation product 4 a along with traces (∼5 %) of the Markovnikov alkenylation product 5 a in 89 % combined yield (Scheme ) .…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal catalyzed olefin hydroarylation or oxidative olefin hydroarylation that does not generate carbocation intermediates offers a strategy for the alkylation or alkenylation of arenes, respectively, that is complementary to current processes. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Along these lines, our groups have been studying a series of neutral ruthenium(II) catalysts with the general formula TpRu(L)(NCMe)Ph (Tp = hydridotris(pyrazolyl)borate; L = CO, PMe 3 , P(pyr) 3 , , P(OCH 2 ) 3 CEt; pyr = N-pyrrolyl) for catalytic ethylene hydrophenylation. [21,[27][28][29][30][31][32][33] In those studies, we demonstrated that more strongly donating ligands "L" result in an increase in the activation barrier for ethylene insertion into Ru-Ph bonds, [27,29,32] and, as a result, ethylene C-H activation, ultimately to form thermally stable and catalytically inactive h 3 -methylallyl complexes, [25,27,29,32] competes with ethylene insertion.…”
Section: Introductionmentioning
confidence: 99%